1994
DOI: 10.1002/art.1780371204
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline disrupts chondrocyte differentiation and inhibits cartilage matrix degradation

Abstract: Objective. The effects of doxycycline were tested in an in vitro system in which the cartilages of embryonic avian tibias are completely degraded.Methods. Tibias were cultured with 5, 20, or 40 pg/ml doxycycline. Control tibias were cultured without doxycycline. Conditioned media and tissue sections were examined for enzyme activity and matrix loss.Results. Cartilages were not resorbed in the presence of doxycycline, whereas control cartilages were completely degraded. Collagen degradation was reduced in assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 39 publications
4
16
0
Order By: Relevance
“…These experiments also demonstrated that the IC 50 levels for tetracyclines to inhibit NOS activity augmented by IL-1␤ were similar to the spontaneous release of NO. The concentrations of doxycycline that inhibited NO production in our studies are comparable to those required for the inhibition of matrix metalloproteases (19,(30)(31)(32)(33). In those studies, doxycycline at 20-50 g͞ml inhibited the activity of proteolytic enzymes such as collagenase and gelatinase, blocked proteoglycan degradation, reduced the cell death associated with proteoglycan loss, and augmented cartilage growth (31).…”
Section: Resultssupporting
confidence: 60%
“…These experiments also demonstrated that the IC 50 levels for tetracyclines to inhibit NOS activity augmented by IL-1␤ were similar to the spontaneous release of NO. The concentrations of doxycycline that inhibited NO production in our studies are comparable to those required for the inhibition of matrix metalloproteases (19,(30)(31)(32)(33). In those studies, doxycycline at 20-50 g͞ml inhibited the activity of proteolytic enzymes such as collagenase and gelatinase, blocked proteoglycan degradation, reduced the cell death associated with proteoglycan loss, and augmented cartilage growth (31).…”
Section: Resultssupporting
confidence: 60%
“…In vitro, 10 M and 30 M doxycycline inhibited cartilage gelatinase activity by 44% and 82%, respectively (1). Degradation of embryonic avian tibias was inhibited by exposure in vitro to a similarly low concentration of the drug, following which collagenase and 62-kd gelatinase were no longer detectable in the spent culture medium (35).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-8 is predominantly expressed by neutrophils, a cell type not present in our culture system. However, low levels of MMP-8 have been demonstrated to be produced by chondrocytes [Cole et al, 1994] and its potential presence in cartilage should not be discounted.…”
Section: Discussionmentioning
confidence: 99%